2020
DOI: 10.1371/journal.pgen.1008722
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorelay BarA/SirA activates the non-cognate regulator RcsB in Salmonella enterica

Abstract: To survive an environmental stress, organisms must detect the stress and mount an appropriate response. One way that bacteria do so is by phosphorelay systems that respond to a stress by activating a regulator that modifies gene expression. To ensure an appropriate response, a given regulator is typically activated solely by its cognate phosphorelay protein (s). However, we now report that the regulator RcsB is activated by both cognate and noncognate phosphorelay proteins, depending on the condition experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…We recently discovered similar coordinate control of surface-based phage immunity and CRISPR–Cas by the Rcs envelope stress response phosphorelay ( 20 ). Interestingly, a recent study in Salmonella discovered that SirA (PigQ in Serratia ) activated the rcsDB operon and that BarA ( Serratia PigW) could phosphorylate the RcsB transcriptional regulator ( 83 ). We have also previously shown that pigQ transcription is quorum sensing-dependent ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently discovered similar coordinate control of surface-based phage immunity and CRISPR–Cas by the Rcs envelope stress response phosphorelay ( 20 ). Interestingly, a recent study in Salmonella discovered that SirA (PigQ in Serratia ) activated the rcsDB operon and that BarA ( Serratia PigW) could phosphorylate the RcsB transcriptional regulator ( 83 ). We have also previously shown that pigQ transcription is quorum sensing-dependent ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…RcsB can also act in combination with other auxiliary transcriptional factors in a phosphorylation dependent or independent manner ( 3 ). In addition, the sensor protein BarA can also activate the RcsB protein in an RcsC- and RcsD-independent manner ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…At first glance this data seems inconsistent. However, it may simply reflect the fact that RcsB is also subject to post-transcriptional regulation, as has been reported recently in other bacteria [37,38]. Although exploring these mechanisms is outside the scope of this study, it is possible that this post-transcriptional regulation of RcsB occurs also in Yersinia, and especially under conditions where bacteria are more sensitive to stress caused by loss of Cpx signalling.…”
Section: Cpxr Inhibits Rcsb Gene Transcriptionmentioning
confidence: 63%